Tecnologias de Informação e Integração Regional: Desafios Institucionais para a Cooperação Sul-Americana na Área de Segurança - Marco Cepik; Carlos Schmidt Arturi (Universidade do Estado do Rio de Janeiro, 2011)
The present article analyzes the role of information and communication technologies (ICTs) in the integration of the South American region, based on a study of regional security issues and cooperation between states. The study thus seeks to examine the scope of ICTs in building mutual trust between states and harmonization between maintenance of the domestic order and regional stability in a scenario marked by suspicion and political and institutional limitations. The argument is that the use of information technologies can contribute to the deepening of political processes, although in practice there is a lack of a coordinated strategy for South American countries to apply such technologies. The development of ICTs by UNASUL and the South American Defense Council thus emerges as an attempt to promote adequate alignment among initiatives for integration of South American countries and greater exchange of information to promote security and stability in the region.